Material parameters design of vehicle body based on three-level factorial design under impact loading. Issue 4 (3rd July 2016) - Hou, Shujuan; Li, Haizhi; Liu, Tangying; Chen, Yuan
ABSTRACT: This paper applied a method of screening active factors to material parameters selection under crashworthiness design criterion. The three-level unreplicated saturated factorial design technique was used to deal with factors screening of material parameters in the nonlinear dynamic system. Three types of experiment statistic methods were utilised to analyse the accuracy of all the analytical factors, named H statistic, P statistic and B statistic. Multiobjective crashworthiness optimisation platform was established with discrete variables of material parameters. Radial basis functions regression model was employed to get fitting curves of analytical objectives so as to reduce design sampling points and improve the design efficiency. NSGA-II served as the optimisation algorithm. Material parameters selection based on three-level unreplicated saturated factorial design extends the range of factor screening in the crashworthiness optimisation design of vehicle body. It not only breaks through the traditional design method of just selecting several experienced variables, but also shortens the design cycles of vehicle body.